2014
DOI: 10.1080/10580530.2014.854097
|View full text |Cite
|
Sign up to set email alerts
|

Connection Overload? A Cross Cultural Study of the Consequences of Social Media Connection

Abstract: Both positive and negative impacts of specific social media channels have been identified, but their cumulative impacts across media and across cultures have not been examined. A connection overload path model was developed from data gathered in Ireland, the United States, and Korea. The magnitude of connection demands reduced negative affect, while connection habits reduced negative outcomes and negative affect. Difficulties controlling connection habits were related to negative impacts on important life acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 65 publications
6
109
0
4
Order By: Relevance
“…For overdependent relationships, however, greater accessibility was associated with worse relational outcomes. More recently, LaRose et al () demonstrated the potential for linking accessibility to automaticity in a study on “connection habits.” The authors report a similar pattern to the Hall and Baym () study in the context of emotional outcomes. More connection demands, coupled with connection habit strength, predicted reduced negative affect over the last week.…”
Section: Internalized Connectednessmentioning
confidence: 99%
“…For overdependent relationships, however, greater accessibility was associated with worse relational outcomes. More recently, LaRose et al () demonstrated the potential for linking accessibility to automaticity in a study on “connection habits.” The authors report a similar pattern to the Hall and Baym () study in the context of emotional outcomes. More connection demands, coupled with connection habit strength, predicted reduced negative affect over the last week.…”
Section: Internalized Connectednessmentioning
confidence: 99%
“…In previous research, deficient self‐observation was evaluated using persistent thoughts toward the Internet as a proxy measure (e.g., Caplan, ; Tokunaga, ). Others have evaluated habits through more direct measures by way of adapting the Self‐Report Habit Index (e.g., LaRose, Connolly, Lee, Li, & Hales, ). The four‐item deficient self‐observation subscale used here included statements from both the persistent thoughts and habit instruments.…”
Section: Studymentioning
confidence: 99%
“…Kietzmann, Hermkens, McCarthy, and Silvestre (2011) defined social media as employing "mobile and webbased technologies to create highly interactive platforms via which individuals and communities 20 ARIEL AND AVIDAR share, co-create, discuss, and modify user-generated content" (p. 241). LaRose, Connolly, Lee, Li, and Hales (2014) also tied social media with information exchanges and defined social media as "communication channels that are used to form or maintain social relationships through the creation and exchange of electronic interpersonal communication" (p. 60).…”
mentioning
confidence: 98%